Algirdas Penkauskas (1931-1985). Personality, pedagogue, scientist - Dzikarienė, V.; Dževečka, A.; Garbačiauskienė, M.; Kregždė, S.; Krukovskis, J.; Kulvičienė, A. (Psichologija, 1987)
The article presents the biography of Algirdas Penkauskas and his essential works.
Keywords: biography; A. Penkauskas